The Flexibility of Oligosaccharides Unveiled Through Residual Dipolar Coupling Analysis - Poveda, Ana; Fittolani, Giulio; Seeberger, Peter H.; Delbianco, Martina; Jiménez-Barbero, Jesús (Frontiers in Molecular Biosciences, 2021)
The intrinsic flexibility of glycans complicates the study of their structures and dynamics, which are often important for their biological function. NMR has provided insights into the conformational, dynamic and recognition features of glycans, but suffers from severe chemical shift degeneracy. We employed labelled glycans to explore the conformational behaviour of a β(1-6)-Glc hexasaccharide model through residual dipolar couplings (RDCs). RDC delivered information on the relative orientation of specific residues along the glycan chain and provided experimental clues for the existence of certain geometries. The use of two different aligning media demonstrated the adaptability of flexible oligosaccharide structures to different environments.